Genetic variation in ABCB1 influences paclitaxel pharmacokinetics in Japanese patients with ovarian cancer. Issue 3 (1st April 2006) - Yamaguchi, H.; Hishinuma, T.; Endo, N.; Tsukamoto, H.; Kishikawa, Y.; Sato, M.; Murai, Y.; Hiratsuka, M.; Ito, K.; Okamura, C.; Yaegashi, N.; Suzuki, N.; et al.
Abstract : Paclitaxel, an antineoplastic agent used for the treatment of ovarian cancer, is metabolized by cytochrome P450 (CYP)3A4 and CYP2C8 and is excreted from cells by ATP-binding cassette (ABCB1) (multi-drug resistance [MDR1], P-glycoprotein). Expression of these proteins is regulated by pregnane X receptor (PXR). Although there are common genetic polymorphisms in the genes encoding these proteins, their effect on the clinical efficacy of paclitaxel is unclear. We therefore examined the relationship of the paclitaxel pharmacokinetics in 13 patients with ovarian cancer to polymorphisms in CYP2C8, CYP3A5, ABCB1, and PXR . We found high interindividual variability in the plasma concentrations of two metabolites, 6α-hydroxypaclitaxel and p -3′-hydroxypaclitaxel. All the patients were genotyped as CYP2C8*1/*1 . Neither the CYP3A5 A6986G ( CYP3A5*3 ) nor the PXR C-25385T alleles were associated with altered plasma concentrations of paclitaxel and its metabolites. ABCB1 T-129C, T1236C, and G2677(A, T), however, was associated with lower area under the plasma concentration–time curve (AUC) of paclitaxel. We also observed a significant correlation between the AUC ( r = −0.721) or the total clearance of paclitaxel (CLtot ) ( r = 0.673) and the ABCB1 mutant allele dosage in each patient. Taken together, our findings suggest that interindividual variability in paclitaxel pharmacokinetics could be predicted by ABCB1 genotyping.